The effects of dependent supplier-customer relationships on supplier's corporate innovation - Jiao, Zhuoran (Nanyang Technological University, 2022)
In the paper, I study the association between two dimensions of dependent supplier-customer relationships (supplier’s dependence and customer’s dependence) and supplier’s corporate innovation. I also engage in the moderating effect of the relationship duration. Using panel data from the Compustat database and the NBER Patent database, I find that the main effects of supplier’s dependence and customer’s dependence on supplier’s corporate innovation are contingent that are moderated by the relationship duration. Specifically, the relationship duration positively moderates the association between supplier’s dependence and supplier’s corporate innovation while negatively moderates the association between customer’s dependence and supplier’s corporate innovation. The findings highlight the importance of dependent supplier-customer relationships and the nature of dynamic changes in supplier-customer relationships. The paper contributes to firms in selecting appropriate strategies to leverage dependence when they take supplier-customer relationships as a source of innovation.